Manajemen Pengembangan Sumber Daya Manusia Pendidikan Islam dan Implikasinya terhadap Mutu Lembaga di MA Al-Azhar Peterongan Jombang - Rofiqi, Mohammad Arif Zainuddin; Ashari, M. Yahya (Lembaga Yasin AlSys, 2025)
The suboptimal implementation of human resource development (HRD) management in Islamic educational institutions—particularly regarding the integration of training and coaching programs with institutional quality improvement—remains a critical challenge. This study aims to describe and analyze the HRD management practices at MA Al-Azhar Peterongan Jombang and their implications for enhancing the quality of Islamic education institutions. A qualitative case study approach was employed, involving the head of the madrasa, teachers, and administrative staff as key informants through in-depth interviews, observations, and document analysis. Data were analyzed thematically through coding, categorization, and interpretation. The findings reveal that HRD management at MA Al-Azhar encompasses four core functions: planning, organizing, implementation, and supervision—all grounded in Islamic values. The HRD programs include professional training, spiritual development, and academic supervision, which positively influence teachers’ motivation, work ethic, and professionalism, although they have not yet fully translated into improved student academic performance. The study suggests that HRD contributes indirectly to institutional quality through the reinforcement of an Islamic work culture. These findings have implications for the development of a spiritually grounded conceptual model of HRD management as a policy reference for sustainable quality improvement in Islamic education, while also enriching the theoretical discourse on Islamic educational management.